PARA ALÉM DO COMÉRCIO: MERCOSUL, DEMOCRACIA E SEGURANÇA REGIONAL - Fuccille, Alexandre [UNESP]; Luciano, Bruno Theodoro [UNESP]; Bressan, Regiane Nitsch (CEDEC, 2021)
In the context of the 30 years of the Southern Common Market (Mercosur), this article seeks to discuss how the bloc has contributed to democratic stability and the promotion of peace in the region since its creation. Although the commercial agenda has relevance in shaping this project and has become its most visible dimension, the creation of Mercosur was fundamental to distend the area of security and defense among the countries of the bloc, seeking to bury mutual mistrust of decades. Moreover, Mercosur helped to promote the consolidation of democracy in the moment of the returning to democratic governments in the region. Regional institutions developed within Mercosur have conferred and still give relevance to peace and democratic protection agendas in the region. Nonetheless, its loose institutions and high dependence on political dynamics of ruling national governments emphasize its current difficulties in advancing in both regional agendas.

No marco dos trinta anos do Mercado Comum do Sul (Mercosul), o presente artigo busca elucidar e discutir como o bloco contribuiu, desde sua formação, com a estabilidade democrática e a promoção da paz regional. Embora a agenda comercial tenha relevância na conformação desse projeto e seja sua face pública mais visível, a criação do Mercosul foi fundamental para distensionar a área de segurança e defesa entre os países do bloco, buscando sepultar desconfianças mútuas de décadas. Ademais, o Mercosul procurou consolidar a democracia em um momento-chave, pós-autoritário, de retorno aos governos democráticos entre os Estados-membros. As instituições regionais desenvolvidas no âmbito do Mercosul conferiram e ainda conferem relevância às agendas de paz e proteção democrática na região. Não obstante, sua baixa institucionalidade e dependência quanto às dinâmicas políticas dos governos em exercício ilustram as dificuldades recentes em avançar nas agendas regionais.
BEYOND TRADE: MERCOSUR, DEMOCRACY AND REGIONAL SECURITY
Keywords: Mercosur; Democracy; Regional Security; Regional Integration; Democratic institutions; South America; Mercosul; Democracia; Segurança Regional; Integração Regional; Instituições Democráticas; América do Sul